High-Performance Optical Fiber Displacement Sensor with Extended Linear Range and Sensitivity - Gorka Zubia; Joseba Zubia; Josu Amorebieta; Gotzon Aldabaldetreku; Asier Zubia; Gaizka Durana (Sensors)
Optical Fiber Displacement Sensors (OFDSs) provide several advantages over conventional sensors, including their compact size, flexibility, and immunity to electromagnetic interference. These features make OFDSs ideal for use in confined spaces, such as turbines, where direct laser access is impossible. A critical aspect of OFDS performance is the geometry of the fiber bundle, which influences key parameters such as sensitivity, range, and dead zones. In this work, we present a streamlined design methodology for azimuthally symmetric OFDSs to improve the linear range of these sensors. The most effective configuration we propose is the pentafurcated bundle, which consists of a central transmitting fiber surrounded by four concentric rings of fibers with different radii. Our experimental results show that the pentafurcated designs increase both the range—up to 10.5 mm—and the sensitivity of the sensor—<semantics>2mm−1</semantics>—while minimizing the dead zone of the sensor (2.5 mm), allowing accurate measurements even at very short distances